2020
DOI: 10.1111/nin.12355
|View full text |Cite
|
Sign up to set email alerts
|

Accent bias: A barrier to Black African‐born nurses seeking managerial and faculty positions in the United States

Abstract: A large number of internationally educated nurses are recruited each year from developing low-income countries to alleviate the nursing shortage experienced by US healthcare organizations (Kingma, 2007; Li, Nie, & Li, 2014). Many of these nurses speak with a non-native accent. As students, they may be considered English as a second language students or English language learners. According to the Pew Research Center, there were 4.2 million Black immigrants living in the United States in 2016, making up 10% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 68 publications
(116 reference statements)
3
24
0
Order By: Relevance
“…This was often linked to the nurses' accents, and the inability or unwillingness of the native-born nurses to listen and understand them. The lack of respect and feelings of dismissal due to foreign accents was discussed in depth by the participants in (Iheduru- Anderson, 2020b). In Iheduru-Anderson (2020b) study, the participants felt that their accents were viewed as a measure of their intelligence and their contributions to the workplace were often disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…This was often linked to the nurses' accents, and the inability or unwillingness of the native-born nurses to listen and understand them. The lack of respect and feelings of dismissal due to foreign accents was discussed in depth by the participants in (Iheduru- Anderson, 2020b). In Iheduru-Anderson (2020b) study, the participants felt that their accents were viewed as a measure of their intelligence and their contributions to the workplace were often disregarded.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of racism directed at EM nurses from many different sources is particularly apparent when considering internationally-educated nurses (IEN), or nurses who originate in non-Western countries and transition to Western workplaces, such as those in the UK, US, Canada or Australia [20,21]. One interview study of Chinese IENs transitioning to the US found several main themes, including "injustice and discrimination" coming from many different sources, including patients, colleagues, managers, and employers [22].…”
Section: Racism In Nursingmentioning
confidence: 99%
“…Nurse leaders must recognize how gender, culture, and class become intertwined with race rather than existing as discrete, separate identities (Waite & Nardi, 2019). Preconceived notions about Black people's abilities converge with competency concerns raised because of race, which interact to create significant barriers to developing and maintaining a successful career in nursing leadership (Iheduru-Anderson, 2020b, 2020c. This discrimination as a result of intersectional status has led to significant disparities for Black nurses within the profession.…”
Section: Nursing Leadershipmentioning
confidence: 99%
“…In fact, several studies have shown that immigrant nurses and nurses of color in the United States continue to experience acts of discrimination and racist comments from colleagues, and patients and their families (Beard & Julion, 2016;Deacon, 2011;Iheduru-Anderson, 2020a, 2020cIheduru-Anderson & Wahi, 2018;Moceri, 2014;Primeau et al, 2014). In some cases, immigrant nurses' accents have been used as reasons for discrimination in the workplace (Iheduru-Anderson, 2020b). In addition, studies have shown that nurses and nurse educators are not comfortable or feel ill-equipped to discuss race (Holland, 2015;Nairn et al, 2004Nairn et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation